1994
DOI: 10.1016/0014-5793(94)01290-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar concentrations of nitric oxide reversibly inhibit synaptosomal respiration by competing with oxygen at cytochrome oxidase

Abstract: Nitric oxide (NO) reversibly inhibited oxygen consumption of brain synaptosomes. Inhibition was reversible, occurred at the level of cytochrome oxidase, and was apparently competitive with oxygen, with half-inhibition by 270 nM NO at oxygen concentrations around 145 PM and by 60 nM NO at around 30 PM Oz. Isolated cytochrome oxidase was inhibited by similar levels of NO. These levels of NO are within the measured physiological and pathological range for a number of tissues and conditions, suggesting that NO inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

53
686
2
10

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 965 publications
(751 citation statements)
references
References 24 publications
53
686
2
10
Order By: Relevance
“…The most direct effect of NO on chondrocytes appears to be the suppression of energy metabolism (4,(11)(12)(13)34,35). Indeed, it is currently hypothesized that one of the main functions of NO is metabolic regulation, which has been determined, in part, by decreased ATP production (11,12), decreased O 2 consumption (11,12), and decreased matrix synthesis (13).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The most direct effect of NO on chondrocytes appears to be the suppression of energy metabolism (4,(11)(12)(13)34,35). Indeed, it is currently hypothesized that one of the main functions of NO is metabolic regulation, which has been determined, in part, by decreased ATP production (11,12), decreased O 2 consumption (11,12), and decreased matrix synthesis (13).…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition can be accomplished by many distinct mechanisms. For example, it has been reported that NO can form stable nitrosyl adducts with reduced iron contained within the heme of the oxygen-binding site of cytochrome c oxidase (complex IV) of the mitochondrial electron transport chain (34,35). This reaction is rapid and highly competitive with oxygen because nanomolar concentrations of NO have been shown to reversibly inhibit synaptosomal Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations